Variação genética para caracteres anatômicos e retração volumétrica e sua correlação com a densidade básica da madeira em uma população base de Eucalyptus camaldulensis Dehn - Santos, Fernando Wergles; De Moraes, Mario Luiz Teixeira [UNESP]; Florsheim, Sandra Monteiro Borges; De Lima, Israel Luiz; Da Silva, Janete Motta [UNESP]; Freitas, Miguel Luiz Menezes; Sebbenn, Alexandre Magno (My University, 2010)
Eucalyptus camaldulensis has great importance in Brazil because of their phenotypic plasticity for different environmental conditions, as soils, altitudes and rainfall. This study is an investigation of a base population of E. camaldulensis from Australia through a progeny test implanted in Selvíria, MS. The trial was established in a randomized block design, with 25 families and 60 replications of single tree plots. Genetic parameters for anatomic traits and volume shrinkage were estimated, as well as their correlations with wood basic density. No significant differences among progenies were observed for the traits studied. The additive genetic variation coefficient at individual and among progeny levels ranged from low (0.26%) to high (16.98%). The narrow sense heritability at individual and family means levels also ranged from low (0.01) to high (0.87). This indicates that some traits are under strong genetic control and can be improved by selection. In the present situation, in order to attain the highest genetic gains, the sequential selection among and within progeny would be recommended.
Genetic variation for anatomic traits and volume shrinkage and their correlation with wood basic density in an Eucalyptus camaldulensis Dehn base population
Keywords: Genetic gains; Heritability; Progeny test; Tree breeding; Variability; AS-soils; Australia; Block designs; Environmental conditions; Eucalyptus camaldulensis; Genetic control; Genetic gain; Genetic parameters; Genetic variation; Phenotypic plasticity; Present situation; Progeny tests; Sequential selection; Volume shrinkage; Wood basic density; Genes; Shrinkage; Genetic engineering